Nomenclatural notes in Anathallis microphyta (Pleurothallidinae, Orchidaceae) - Santos, Milena C.; Toscano De Brito, A. L. V.; Amano, Erika; Smidt, Eric C. (Phytotaxa, 2018)
In the course of preparing a generic treatment of the genus Anathallis for Flora do Paraná, southern Brazil, historical material and literature of several taxa related to Anathallis microphyta have been studied and their morphologies and nomenclature elucidated. Three species and one variety are proposed as synonyms: Anathallis longiglossa, A. microgemma, A. paranaensis and A. microphyta var. missionum. Illustrations, an updated synonym list, and taxonomic discussions are also provided.